Study of Maximizing Profits in Perfect Competition - Jiang, Wenyuan (Transactions on Economics, Business and Management Research, 2024)
The concept of a perfectly competitive market is one of the foundational theories in microeconomics. This model provides a clear framework for understanding supply, demand, and price determination. In this market structure, many small firms sell almost the same products and compete with each other. As a result, there is no big firms that have significant market power to change the market price. This idea was first come up by economists such as Adam Smith. This paper explores how a firm can maximize profits and minimize costs using Calculus, particularly derivatives and integrals. It will provide a clear derivation process and explain each step in detail. Moreover, this research discusses real-world economic problems related to pricing and cost structures, using bakery as an example. By addressing these multifaceted issues, the study strives to give a better suggestion to small businesses in the Perfect Competition about management strategies to ensure a comparatively stable economic environment for business growth. Then the failure rate can be reduced.